A Review on Recent Advances in Electrochromic Devices: A Material Approach. Issue 8 (28th May 2020) - Rai, Varun; Singh, Ram Sevak; Blackwood, Daniel John; Zhili, Dong
Abstract : Electrochromic (EC) device reversibly changes color and optical state by applying electric potential. EC materials shows color change due to redox process and electron transfer across various states under influence of electric field. EC devices are categorized based on various classes of EC materials inorganic metal oxide and polyoxometalates (POMs), metal complexes, hybrid materials, metal plasmonics–metal/alloy and organic molecules/conjugated polymers. EC materials and its viability for device application are presented herein considering various performance parameter indices. The performance of EC devices is monitored by its switching time between transparent‐bleached state to colored state and vice versa, cycling stability, coloration efficiency, applied voltage, electro‐optical properties, electrochemical stability and breakdown potentials of EC materials and electrolytes. Recent advances in the area of EC devices and materials, its operation mechanism in various categories of EC materials along with existing challenges and recommendations to improve performances and reliability are summarized. Abstract : Recent advances in electrochromic (EC)devices are discussed, emphasizing materials, device operation mechanism in various category of EC materials along with existing limitations and recommendations to improve performances and reliability.